ANALISIS KEBOCORAN SISTEM HIDROLIK PADA LANDING GEAR PESAWAT AIRBUS A330 SERIES MENGGUNAKAN METODE PDCA - Yudhi Chandra Dwiaji (Politeknik Negeri Ketapang, 2021)
The landing gear of the Airbus 330 uses a green hydraulic system, which is currently still found several leaks which result in a decrease in flight safety because the propulsion force on the landing gear does not function normally so it must use the freefall system when landing. This study analyzes the events that cause leaks of the flexible hose system, swivel valve and pitch trimmer. Flexible hose in AircraftmMaintenance Manual has no limitations when a rapture occurs, while for swivel and pitch trimmers there are still limitations. The hydraulic system leak data was taken in January – December 2020 with a total of 49 cases of leaking hydraulic system cases in the landing gear area, where flexible hose has a very high leakage rate compared to other cases. To identify the causes of hydraulic system leaks, this study used ultrasonic internal leak measurement tools and hydraulic fluid analysis methods.